THE IMPLEMENTATION OF JAVANESE LANGUAGE DEPICTED AS THE DISCRIMINATIVE USE - Putri, Novita Sumarlin (Universitas Muhammadiyah Tapanuli Selatan, 2024)
Abstract This paper discussed the implementation of Javanese language and the impact of the use. The writer did this study by the literature review. 25 text books are used as sources the data. Then, the writer made the summary from the review. Through the review, there is speech of levels in Java called by unggah-ungguhing basa (speech levels). Commonly the Javanese language is divided into three level; they are ngoko (rude), madya (middle in use) and krama (refined). Each of them shows difference in use based on Javanese social status. It can be classified into social stratification which is system placement of social class based on the different rights. Social stratification causes discrimination especially in class discriminative and social distance in society. To realize about that discrimination, we have to understand about the basic of human right.Key word: Discrimination, Javanese language, social stratification